Produção de pastagens de trigo e azevém com diferentes doses de adubação nitrogenada em cobertura - Timm, Luiz Carlos (2018)
With the need to increase world food production, motivated by population growth, and better use of arable land, it is important to increase productivity and land use, which is a high cost. The objective of this study was to study the dry matter production of dual-purpose wheat BRS Tarumã (Triticum aestivum) and annual ryegrass (Lolium multiflorum) pastures, managed with different doses of nitrogen fertilization in the topdressing and evaluate the adjustment to the exponential growth model. These winter crops contribute to better land use, and dilute costs when well managed. Nitrogen is one of the mineral elements of greatest need for the development of the plants. In this way, experiments were carried out at the Instituto Sul Sul Riograndense, Campus Pelotas Visconde da Graça (CaVG), located in Pelotas - RS, where for each species, completely randomized with four replicates per treatment with plots of 9m2 of floor space, in which treatments were distributed: 0, 150, 250, 350 and 450 kilograms of nitrogen per hectare applied in a piecemeal way in urea and ammonium sulfate. We emphasize that the species were not compared among themselves, since they present genetics for distinct aptitudes, that is, BRS Tarumã wheat was developed for grazing and grain production. The annual BRS Ponteio ryegrass was developed for grazing. The cultivars analyzed without nitrogen application had limited growth and showed no adjustment even to the first order linear model. The nitrogen application impacted in order to reduce the interval between cuts and increased dry matter production per hectare following the exponential growth model.